Integration of postmodern perspectives in curriculum & instruction in Ethiopian schools - Matheas Shemelis; Tamirat Tadesse; Ambissa Kenea (Cogent Education)
Several studies conducted in Ethiopia on the issues of quality education, methodology, academic performance, and school leadership. However, there is no adequate and organized evidence showing the inclusion of postmodern perspectives in the curriculum and instruction of Ethiopian schools. The aim of this study was to systematically analyze the fragmented research conducted in Ethiopia and how the postmodern perspectives are integrated into the curriculum and instruction. The review used 24 research articles and four policy documents as a data source. The result shows that Ethiopia’s educational policy considers postmodern perspectives in its philosophy of education, curriculum development, and implementation strategy. However, the actual practice of education was far behind meeting the intention of the policy. The factors for the gap are attributed to scarce resources and poor infrastructure, poor quality of teachers and school leaders, the multidimensional nature of problems and reductionist views of solutions, and lack of transparency and accountability. Furthermore, the study found that policy-level consideration of postmodern perspectives, teachers’ knowledge and understanding of the perspectives, and globalisation and technological advancement promise to integrate postmodern perspectives in the curriculum and instruction of Ethiopian schools. Finally, implications for practice and further research are discussed, and recommendations are made to bridge the gap between policy, curriculum, and classroom practices.